Religiöse Schiedsgerichtsbarkeit: angloamerikanische Rechtspraxis, Perspektive für Deutschland - Hötte, Franziska (Jus Ecclesiasticum, 2013)
Based on the legal framework, practical examples and a critical analysis of the debate on religious arbitration in the United Kingdom, Canada and the USA, the author shows how religious courts operate in secular constitutional states, what procedural rules they follow and what constitutional concerns have to be taken into account when enforcing religious arbitration awards. She concludes by examining whether the religious arbitration of family law disputes could also take place in Germany.